Preoperative Education and Use of Analgesic Before Onset of Pain Routinely for Post-thoracotomy Pain Control Can Reduce Pain Effect and Total Amount of Analgesics Administered Postoperatively - ALPAR, ŞULE (ELSEVIER SCIENCE INC, 2014)
The purpose of this study was to investigate the efficiency of preoperative pain management education and the role of analgesics administration before the onset of pain postoperatively. The study was a prospective, randomized, and single-blind clinical trial, which was conducted January 1, 2008 through October 1, 2008 in the Thoracic Surgery Unit of Akdeniz University Hospital. A total of 70 patients who underwent thoracotomy (35 in the control group and 35 in the study group) were included in the study. Of the patients, 70% (n = 49) were male and 30% (n = 21) were female. Mean age was 51 +/- 10 years (range 25-65). The same analgesia method was used for all patients; the same surgical team performed each operation. Methods, including preemptive analgesia and placement of pleural or thoracic catheter for using analgesics, that were likely to affect pain level, were not used. The same analgesia medication was used for both patient groups. But the study group, additionally, was educated on how to deal with pain preoperatively and on the pharmacological methods to be used after surgery. An intramuscular diclofenac Na 75 mg was administered to the study group regardless of whether or not they reported pain in the first two postoperative hours. The control group did not receive preoperative education, and analgesics were not administered to them unless they reported pain in the postoperative period. The routine analgesics protocol was as follows: diclofenac Na 75 mg (once a day) intramuscular administered upon the complaint of pain following extubation in the postoperative period and 20 mg mepederin intravenously (maximum dose, 100 mg/day), in addition, when the patient expressed pain. Pain severity was assessed during the second, fourth, eighth, 16th, 24th, and 48th hours, and marked using the Verbal Category Scale and the Behavioral Pain Assessment Scale. Additionally, the total dose of daily analgesics was calculated. The demographic characteristics showed a homogeneous distribution in both patient groups. The rate of pain, which was defined as sharp, stabbing, and exhausting, was higher in the control group than in the study group, and the difference between the two groups was statistically significant (p < .05). As the doses of analgesics used for pain management in both groups were compared, it was determined that analgesic consumption was lower in the study group than in the control group, and the difference was statistically significant (p < .05). As a result, it was determined that preoperative thoracic pain management education and analgesics administered postoperatively, before the onset of pain, reduced the amount of analgesics used in the first postoperative 48 hours. Crown Copyright (C) 2014 Published by Elsevier Inc. on behalf of the American Society for Pain Management Nursing
Keywords: NONSTEROIDAL ANTIINFLAMMATORY DRUGS; EPIDURAL ANALGESIA; MANAGEMENT; SATISFACTION; INTENSITY; ANXIETY; RELIEF; IMPACT